Science, technology, engineering, mathematics education: In-service sicence teachers’ Views, attitudes anda readiness readiness - Bektaş, Rukiye (My University, 2019)
The aim of the study is to reveal in-service science teachers’ attitudes, views and readiness for STEM education. For this aim, this study was conducted in two parts. In the first part, in order to examine attitude and readiness of the in-service science teachers, T-STEM survey [69] which consists of 9 different parts, was implemented on the participants. In the second part, semi-structured interviews which consist of 6 questions were done to reveal views of the participants. This study was conducted with 80 in-service science teachers who work in public or private schools. Sample of this research consists of 20 male and 60 female volunteer in-service science teachers with a mean age of 29. In service science teachers who are participated to study have different educational backgrounds. Also, they had on average 2-5 years of teaching experience. Some of the participants have prior experience on teaching STEM. To analyze first part of the data different parametric tests such as t-test, one-way analysis of variance (ANOVA) and correlation analysis were used. For the second part of the data, content analysis technique was used by the researcher. II The results of the analysis indicated that 25% of the participants had STEM education and others did not. Although many of them did not have any STEM education beforehand, most of the in-service science teachers have positive attitude towards STEM education according to their hearings about STEM. They believe that this approach will increase success of the students. Participants who had STEM education used STEM in their classes. However, they stated that physical circumstances of the schools, readiness of the in-service science teachers in Turkey is not enough to apply STEM education yet. Besides, participants who did not have STEM education stated that they do not know how to teach with STEM so that they do not feel confident enough to lead students to follow STEM related career paths. As a result of these, participants stated that there is need of content knowledge, practice guideline, experience opportunity and suitable physical conditions to teach with using STEM.

Bu çalışmanın amacı, hizmet içi fen bilgisi öğretmenlerinin FeTeMM eğitimine yönelik tutumlarını, görüşlerini ve hazırbulunuşluklarını ortaya koymaktır. Bu amaçla, bu çalışma iki bölüm halinde yürütülmüştür. Birinci bölümde fen bilgisi öğretmenlerine, tutum ve hazırbulunuşluklarını ölçmek amacıyla 9 farklı bölümden oluşan T-STEM anketi [69] uygulanmıştır. İkinci bölümde ise katılımcıların FeTeMM eğitimi ile ilgili görüşlerini detaylı olarak ortaya koymak için 6 yarı yapılandırılmış sorudan oluşan görüşmeler yapılmıştır. Araştırmacı bu çalışmayı kamu ve özel okullarda çalışan 80 hizmet içi fen bilgisi öğretmeni ile gerçekleştirmiştir. Araştırmanın örneklemini, yaş ortalaması 29 olan 20 erkek ve 60 kadın gönüllü fen bilgisi öğretmeni oluşturmaktadır. Araştırmaya katılan hizmet içi fen bilgisi öğretmenlerinin farklı eğitim geçmişleri ve ortalama 2-5 yıllık öğretim deneyimleri vardır. Katılımcılardan bazıları, FeTeMM öğretimi konusunda önceden deneyime sahiptir. Verilerin ilk kısımlarını analiz etmek için t-testi, tek yönlü varyans analizi (ANOVA) ve korelasyon analizi gibi farklı parametrik testler kullanıldı. Verilerin ikinci kısmının analizi için araştırmacı tarafından içerik analizi tekniği kullanılmıştır. Analiz sonuçları, katılımcıların %25'inin FeTeMM eğitimi aldığını ve diğerlerinin almadığını göstermektedir. Bu duruma rağmen araştırma sonuçları gösteriyor ki hizmet içi fen bilgisi öğretmenlerinin çoğu FeTeMM eğitimi ile ilgili duyduklarından yola çıkarak FeTeMM eğitimine karşı olumlu tutum içerisindeler. Bu yaklaşımın öğrencilerin başarılarını artıracağına inanıyorlar. Ayrıca önceden FeTeMM eğitimi almış olan katılımcılar FeTeMM'i sınıflarında kullandıklarını ancak, okulların fiziki koşullarının ve Türkiye'deki hizmet içi fen bilgisi öğretmenlerinin hazırbulunuşluklarının henüz FeTeMM eğitimini uygulamak için yeterli olmadığını belirttiler. Ayrıca, FeTeMM eğitimine sahip olmayan katılımcılar, FeTeMM konusunda eğitim vermek ve bu alandaki mesleklere öğrencileri yönlendirmek konusunda gerekli öz yeterliliğe sahip olmadıklarını belirttiler. FeTeMM eğitimi, öğretim rehberi, deneyim fırsatı ve uygun fiziksel koşullara ihtiyaç olduğunu eklediler.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: STEM education; In-service science teachers; Readiness; Attitudes; FeTeMM eğitimi; Hizmet içi fen bilgisi öğretmenleri; Hazırbulunuşluk; Tutum